2015
DOI: 10.1111/aas.12508
|View full text |Cite
|
Sign up to set email alerts
|

Stress ulcer prophylaxis in the intensive care unit: an international survey of 97 units in 11 countries

Abstract: In this international survey, most participating ICUs reported using SUP, primarily proton pump inhibitors, but many did not have a guideline; indications varied considerably and concern existed about infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 38 publications
5
65
1
5
Order By: Relevance
“…While there is variation in practice worldwide, several surveys showed that PPIs are the most frequently used agents in North America, Australia, and Europe, followed by H2RAs [540][541][542][543][544]. A recent meta-analysis including 19 RCTs (n = 2177) showed that PPIs were more effective than H2RAs in preventing clinically important GI bleeding (RR 0.39; 95% CI 0.21-0.71; p = 0.002; moderate quality), but led to a nonsignificant increase in pneumonia risk (RR 1.17; 95% CI 0.88-1.56; p = 0.28; low quality) [544] prior meta-analyses reached a similar conclusion [545,546].…”
Section: S Stress Ulcer Prophylaxismentioning
confidence: 99%
“…While there is variation in practice worldwide, several surveys showed that PPIs are the most frequently used agents in North America, Australia, and Europe, followed by H2RAs [540][541][542][543][544]. A recent meta-analysis including 19 RCTs (n = 2177) showed that PPIs were more effective than H2RAs in preventing clinically important GI bleeding (RR 0.39; 95% CI 0.21-0.71; p = 0.002; moderate quality), but led to a nonsignificant increase in pneumonia risk (RR 1.17; 95% CI 0.88-1.56; p = 0.28; low quality) [544] prior meta-analyses reached a similar conclusion [545,546].…”
Section: S Stress Ulcer Prophylaxismentioning
confidence: 99%
“…Other recent research shows a growing use of PPIs as the primary SUP agent, ranging from 39-70%. 6,9,10,12 This may reflect perceived superiority of PPIs as indicated in a recent systematic review and meta-analysis. The study at issue showed that PPIs were associated with a 60% relative risk reduction in clinically important stress ulcer-related GI bleeding when compared with H2RAs.…”
Section: Discussionmentioning
confidence: 99%
“…ICU = intensive care unit; NPO = nil per os; SUP = stress ulcer prophylaxis discontinue SUP upon discharge from the ICU, and only 13% discontinue SUP after tracheal extubation. 10 The prevailing impression of many physicians is that the clinically important GI bleeding rate has decreased over time in the ICU, whether due to prevalent acid suppression in the community and in the hospital setting or improvements in resuscitation and the use of enteral nutrition. Over 20 years ago, only 2% of critically ill patients had clinically important bleeding while receiving SUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of non-ICU high-risk patients may also add to the questioned role of mechanical ventilation as a trigger of stress ulcers. Despite the clinical equipoise, common beliefs and practices across various medical specialties are that certain subpopulations of acutely ill patients benefit from stress ulcer prophylaxis [31]. …”
Section: Introductionmentioning
confidence: 99%